The moderating effect of emotional competence on job satisfaction and organisational commitment of healthcare professionals - Elena Stamouli; Sebastian Gerbeth (BMC, 2021)
Abstract Background Healthcare organisations, such as hospitals, are largely seen as task-oriented, width different people expected to work in interdependent teams. The objective of this study was to investigate the relevance of individual factors (job satisfaction) and individual competences (emotional competence) for organisational commitment in a sample of healthcare professionals. Methods A cross-sectional survey was conducted among 96 healthcare professionals from March to June 2018 in the catchment area of five clinics in Bavaria, Germany. The present research examined the moderating role of emotional competence on the relationship between job satisfaction and organisational commitment using moderated regression analysis and simple slope analysis. Results Multiple regression analysis indicated that emotional competence moderated the relationship between satisfaction with the job and commitment to the job. The results showed that healthcare professionals with high emotional competence are able to deal more effectively with dissatisfaction in the workplace so that organisational commitment remains unaffected. Conclusions Based on the findings of this study emotional competence of healthcare professionals is important for increasing job satisfaction and commitment to the job. Especially for healthcare professionals whose job satisfaction is low, a high level of emotional competence enables them to maintain a high level of organisational commitment. The findings of the study are discussed at the theoretical level for researchers and practical level for hospital managers interested in fostering emotional competence and improving healthcare professionals' job satisfaction and their organisational commitment, which ultimately may lead to effective performance.